(3aUd GdebGd aj TQM cJGH GdCeKGds - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s
(3ChdgG (B:s
(3hEfeG CQGO GdfHj (B((3U(B) (3bhd Gddg JYGdi (B"(3adjfXQ GdEfSGf ee Ndb(B" s
(3BNQgG (B:s
(3hjJSGhi QajYge hhVjYge, HdZJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B90 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs